Data: Fatigue crack growth behavior in an aluminum alloy Al–Mg–0.3Sc produced by wire based directed energy deposition process - Ye, Jin; Khadar Syed, Abdul; Zhang, Xiang; Eimer, Eloise; Williams, Stewart W. (Cranfield University, 2023)
Additive manufacturing (AM) of Al-Mg-Sc alloys has received considerable interest from the aerospace industry owing to their high specific strength and suitability for AM. Since damage tolerance is a mandatory requirement for safety critical aerospace structures, this study has investigated the fatigue crack growth behaviour in an Al-Mg-0.3Sc alloy made by the wire and arc additive manufacturing. Tests were conducted with two different crack orientations at load ratios 0.1 and 0.5. At the lower load ratio and lower stress intensity factor range (10 MPa m1/2, isotropic crack growth rate property was measured; grain size effect was overcome by the mechanical factor (the stress intensity factor). At the higher load ratio 0.5, both the threshold and the critical values of the stress intensity factor range were reduced. Finally, the modified Hartman-Schijve equation was successfully employed to represent the crack growth rates including the threshold and the fast crack growth regions.
Keywords: 'Wire and arc additive manufacturing (WAAM)'; 'Al-Mg-Sc alloy'; 'fatigue crack growth'; 'microstructure'; 'Hartman-Schijve equation'